2013
DOI: 10.2166/wst.2013.487
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of methylene blue and Congo red from aqueous solution by activated carbon and carbon nanotubes

Abstract: This study was conducted to determine the adsorption removal of dyes by powdered activated carbon (PAC, Norit) and multi-walled carbon nanotubes (MWCNTs, Chinese Academy of Science) from an aqueous solution. Methylene blue (MB) and Congo red (CR) were selected as model compounds. The adsorbents tested have a high surface area (PAC 835 m(2)/g, MWCNTs 358 m(2)/g) and a well-developed porous structure which enabled the effective treatment of dye-contaminated waters and wastewaters. To evaluate the capacity of PAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 6 publications
1
25
0
Order By: Relevance
“…The kinetic study revealed that adsorption of both dyes was faster in initial stages and then become constant. The pseudo‐second order model describes the adsorption kinetics of both dyes . The magnetic nanoparticles gained much attention as they can be easily recovered from solution with the help of external magnet.…”
Section: Removal Of Organic Contaminants Using Nanomaterialsmentioning
confidence: 98%
See 1 more Smart Citation
“…The kinetic study revealed that adsorption of both dyes was faster in initial stages and then become constant. The pseudo‐second order model describes the adsorption kinetics of both dyes . The magnetic nanoparticles gained much attention as they can be easily recovered from solution with the help of external magnet.…”
Section: Removal Of Organic Contaminants Using Nanomaterialsmentioning
confidence: 98%
“…The pseudosecond order model describes the adsorption kinetics of both dyes. [16] The magnetic nanoparticles gained much attention as they can be easily recovered from solution with the help of external magnet. Recently, T. Ahamadand and his co-workers prepared amine functionalized MWCNTs by chemical modification method and then magnetic nanoparticles were embedded into it.…”
Section: Carbon Nanotubes Based Nanomaterials In Removal Of Dyesmentioning
confidence: 99%
“…It is therefore possible to form a non-covalent pi-pi interaction between CR molecules and the graphene surface of carbon nanotubes. Reports can be found in literature on the interaction of CR with carbon nanotubes [28][29][30][31] and the surface of graphene oxide [32,33].…”
Section: The Interaction Of Congo Red With Carbon Nanotubesmentioning
confidence: 99%
“…In another paper [31] authors point to the possibility of using CNT for adsorbing dyes from aqueous solutions -in post-production wastes containing textile dyes. CR was used as a model compound in these studies and the results show an effective binding of CR by carbon nanotubes (with a maximum adsorption of 500 mg/g).…”
Section: The Interaction Of Congo Red With Carbon Nanotubesmentioning
confidence: 99%
“…A less known approach is based on the interaction of CNTs with a bis-azo dye – Congo red (CR) [27]. This original procedure was based on the prolonged (2 hours) manual grinding of CR and purified SWNTs in agate mortar with the addition of water to avoid agglomeration of dried CR powder.…”
Section: Introductionmentioning
confidence: 99%